2017
DOI: 10.21037/cdt.2017.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular versus surgical treatment for acute limb ischemia: a systematic review and meta-analysis of clinical trials

Abstract: In patients presenting with ALI (<2 weeks of duration), ENDO and SURG approaches have similar rates of short-term and 12 month mortality, limb amputation and recurrent ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Some clinical trials and single‐centre studies have reported low rates of failure for endovascular and surgical interventions, but in registries and clinical studies that included heterogeneous groups of patients with PAD, acute occlusion of revascularization procedures during long‐term follow‐up has been reported commonly. Previous revascularization is an important risk factor for the development of acute ischaemia, which can frequently stimulate requirement for major amputation. Thus, the short‐term benefits of revascularization, in terms of symptom relief, may potentially be offset by the longer‐term hazards of major amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials and single‐centre studies have reported low rates of failure for endovascular and surgical interventions, but in registries and clinical studies that included heterogeneous groups of patients with PAD, acute occlusion of revascularization procedures during long‐term follow‐up has been reported commonly. Previous revascularization is an important risk factor for the development of acute ischaemia, which can frequently stimulate requirement for major amputation. Thus, the short‐term benefits of revascularization, in terms of symptom relief, may potentially be offset by the longer‐term hazards of major amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Level References I A The STILE trial (1994), 91 Comerota et al (1996), 100 Enezate et al (2017), 11 Ouriel and Veith (1998), 101 Bath et al…”
Section: Classmentioning
confidence: 99%
“…Another recent systematic review reported similar results, with no evidence in favour of either thrombolysis or surgery. 11 The risks of surgery and thrombolysis in the initial treatment of ALI are presented in a meta-analysis. This analysis also supplies the background for the medical guidelines of the American College of Chest Physicians.…”
Section: Primary Open Surgery or Thrombolysis For Acute Limb Ischaemia?mentioning
confidence: 99%
“…Fluid resuscitation, pain control, and unfractionated heparin can be utilized to temporize the patient until definitive management can occur [ 4 ]. In patients presenting with ALI, the endovascular therapy and surgical revascularization approaches have similar rates of short-term and 12-month mortality, limb amputation, and recurrent ischemia [ 10 ].…”
Section: Discussionmentioning
confidence: 99%